2022
DOI: 10.3389/fmicb.2022.837776
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Aspergillus fumigatus Germination by Neutrophils Is Enhanced by Endothelial-Derived CSF3 Production

Abstract: Infection with Aspergillus fumigatus can cause life-threatening diseases in immunocompromised patients with an unacceptable mortality rate. Angioinvasion is one of the features of severe invasive aspergillosis. Neutrophils are short-lived immune cells regulated by colony-stimulating factor 3 (CSF3) that play a key role in anti-fungal immune responses. To investigate the interactions between A. fumigatus and the host immune cells, such as neutrophils, we stimulated human umbilical vein endothelial cells (HUVECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The changes in some chemokines’ trends ( Figure 3 ) and increased proportion of neutrophils in infected G2A -/- mice ( Figure 4B ) suggested a prominent role of neutrophils in enhancing the survival of G2A -/- mice. Thus, we asked if granulocyte cell stimulating factor (G-CSF) levels could be altered in infected G2A -/- mice in comparison to G2A +/+ as G-CSF is important for neutrophil survival, proliferation, and differentiation ( 44 , 45 ) and was recently shown to be involved in the suppression of A. fumigatus germination ( 45 ). It is also involved in damaging hyphae of A. fumigatus by enhancing the neutrophil oxidative burst ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in some chemokines’ trends ( Figure 3 ) and increased proportion of neutrophils in infected G2A -/- mice ( Figure 4B ) suggested a prominent role of neutrophils in enhancing the survival of G2A -/- mice. Thus, we asked if granulocyte cell stimulating factor (G-CSF) levels could be altered in infected G2A -/- mice in comparison to G2A +/+ as G-CSF is important for neutrophil survival, proliferation, and differentiation ( 44 , 45 ) and was recently shown to be involved in the suppression of A. fumigatus germination ( 45 ). It is also involved in damaging hyphae of A. fumigatus by enhancing the neutrophil oxidative burst ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…In mouse infections, G-CSF administration has been overall effective in protecting non-neutropenic mice from invasive candidiasis and is effective for mice with less severe neutropenia infected with A. fumigatus ( 46 ). Recent work has shown that G-CSF enhances the suppression of A. fumigatus germination ( 45 ). Our work shows that G2A may dampen neutrophilic recruitment during initial inflammation with A. fumigatus.…”
Section: Discussionmentioning
confidence: 99%
“…Murine neutrophils also phagocytose and kill Aspergillus conidia via Dectin-1 and CARD-9 depending on Syk-kinase signaling and downstream NADPH oxidase-induced ROS production [56]. In addition, neutrophils release antimicrobial peptides, proteases, and neutrophil extracellular traps (NET) to avoid fungal invasion [57]. The ROS also mediates release of neutrophil extracellular traps (NETs) [58].…”
Section: Fungal Pulmonary Diseasesmentioning
confidence: 99%
“…However, in immunocompromised patients, lung epithelial cells have a reduced ability to clear spores, leading to increased adhesion and germination of A. fumigatus ( 6 ). Some studies have shown that A. fumigatus infects lung epithelial cells in vitro , first adhering to the cell surface, followed by internalization into the cell, and after 6 h of infection, its spores begin to germinate budding tubes, known as small hyphae, which in turn cause an invasive infection and recruit professional phagocytes such as macrophages and neutrophils to the site of infection ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%